Sex playing with the mind: effects of oestrogen and testosterone on moon and cognition - OSVALDO P. ALMEIDA (Arquivos de Neuro-Psiquiatria)
Women now spend more than 1/3 of their lives in a state of oestrogen deprivation as a result of increased life expectancy. A similar, but milder, hypogonadal state has been described for elderly men. This paper aims to review the available literature on the effects of both oestrogen and testosterone on mood and cognition. Oestrogen replacement therapy of postmenopausal women is associated with improvements in measures of well being and decline in depression scores. In addition, oestrogen seems to augment the response of postmenopausal women with major depression to antidepressant treatment. Most studies designed to investigate the impact of oestrogen on cognition indicate that replacement therapy is associated with better performance on neuropsychological tests, particularly in measures of verbal memory and fluency. The data also supports claims that oestrogen replacement therapy reduces the risk of Alzheimer's disease in later life and improves response of patients to anticholinesterase treatment. Data on the effects of testosterone is sparser. Preliminary findings suggest that testosterone therapy may improve mood when used in isolation or in association with oestrogen. The effects of testosterone on cognitive functioning are less clear - some studies indicate that the administration of testosterone to non-demented subjects is associated with better visuospatial functioning and deterioration of verbal skills. In summary, gonadal hormones seem to modulate various aspects of mental functioning. If future studies prove this to be true, hormone replacement therapy should have a major impact on the physical and mental health of older people in the years to come.